A Five year financial plan for Trimec Trading Corporation - Mariel Angelica A. Dimaano, Ma. Camille O. Angel, Roxanne R.Gonzales, Christine Joy T. Gulapa, Marylyn R. Lagunzad, Gamaliel nIvan M. Ruiz, and Gracil Aiko V. Valendez. 4 0 16; 5
EXECUTIVE SUMMARY: Trimec Trading Corporation is a company known for conceptualizing the first free standing popcorn retail outlet through food retail carts. The company can boost as well of being the market leader for microwave popcorn. The company exposes high revenue, but manifests high operating expenses which swallowed up the revenue, resulting to a minimal net income. This is due to high rental expense which has the greatest part in operating expense. To aid the company in solving ascertained problems, the proponents have come up with alternative course of action that will also help to attain the company's financial objectives. Specifically, the company will be acquiring property to be used as plant, warehouse and office. This course of action will help the company to reduce the company's expenses for rental and thereby lessen operating expenses and significantly increase the net income. This would entail funding through consumption of retained earnings appropriated for future expansion. Hence, the amount saved from renting would be used to pay off the obligations incurred by the company as well as to recover the fund spent in building the warehouse and office. After paying off the obligation and recovering the cost for the acquisition of the project, the savings gained from the rental expenses could be added to the company's net income. In a nutshell, this course of action when executed will be beneficial to lessen the company's operating expenses.
Financial Plan: (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2